The Discipline of Subjectivity : An Essay on Montaigne - Bencivenga, Ermanno, 1950- (Book collections on Project MUSE., 1990)
Through an interpretation of Montaigne's philosophical vision as expressed in his Essays, Ermanno Bencivenga contributes to the current debate about the "death of the subject" by developing a view of the self as a project of continuous construction rather than the source and foundation of knowledge. This latter, Cartesian conception of self-consciousness as a logical and epistemological starting point is, Bencivenga contends, delusive: the certainty it provides is more akin to faith than to a cognitive state. How then do we acquire knowledge of the self? Montaigne makes for a productive case study in this regard: he declares that he himself is the matter of his book, and that nothing but the constitution of his own self is his business. A study of Montaigne reveals that the fundamental category missing in the Cartesian conception of the self is that of practical effort. The self is not a ready-made entity, available for inspection and analysis, but something whose generation requires exercise, training, and discipline. It is the result of an operation that must be performed not just once, but, as in all training, over and over again until it becomes second nature. Bencivenga characterizes the particular training required by the project of constituting a subject as a revolutionary, transgressive, critical one, which shares with philosophical activity a profoundly playful irrelevance to the "ready to hand."Originally published in 1990. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905